Outcome of transanal endorectal vs. transabdominal pull-through in patients with Hirschsprung’s disease - Romero, Philipp; Michalke, Michaela; Chmelnik, Martin; Königs, Ingo; Wessel, Lucas; Holland-Cunz, Stefan (Langenbeck's archives of surgery, 2011)
Introduction: Various outcomes have been reported in patients with Hirschsprung’s disease (HD) following transanal endorectal (TERPT) or conventional transabdominal (ABD) pull-through procedures. This study examined postoperative complications and the long-term outcome of TERPT vs. ABD pull-through for HD. Methods: Records were reviewed for 53 patients over 3 years of age in whom a pull-through procedure was performed for HD (TERPT, n = 24; ABD, n = 29) between 1992 and 2007 at the Departments of Pediatric Surgery, University of Heidelberg and University Hospital of Mannheim, and their families were interviewed and scored via a thorough 15-item, post-pull-through, long-term outcome questionnaire. Total scores ranged from 0 to 40: 0 to 10, excellent; 11 to 20, good; 21 to 30, fair; and 31 to 40, poor. Two-sided Fisher’s exact test and analysis of variance were used to compare different variables in patients in the two groups with significance set at p < 0.05. Results are expressed as mean and standard deviation (SD). Results: Overall scores were similar (TERPT, n = 16, 7.3 +/− 6.6 vs. ABD, n = 23, 4.6 +/− 3.5, p = 0.11) and showed mainly excellent or good long-term outcome for TERPT (93.8%) and ABD (99.7%) pull-through procedures. The incidence of incontinence in children older than 3 years was insignificantly lower in ABD group (TERPT 18.7% vs. ABD 4.3 %, p = 0.15). Regarding the soiling score, however, the soiling tended to be significantly more severe after TERPT than ABD. For the TERPT procedure, the appearance of postoperative constipation, enterocolitis, anastomotic dehiscence, and symptomatic anastomotic stricture was lower but this was not statistically significant. After TERPT, patients started to feed sooner (TERPT 2.8 days vs. ABD 4.4 days, p = 0.005) and operating time (TERPT 133.2 min vs. ABD 204 min, p < 0.001) and hospital stay (TERPT 9.8 days vs. ABD 17.7 days, p < 0.001) were significantly shorter. Conclusion: We employ the TERPT procedure as the first choice in children with rectosigmoid HD.